Congenital melanocytic nevus. Clinical and dermoscopic signs of malignancy. - Milano, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
Prepubertal melanoma has an incidence of 0.8 per million. Congenital melanocytic nevi (CMN) are the most frequent predisposing factor to the prepubertal melanoma in cases where a predisposition is detectable. The clinical and dermoscopic criteria leading to suspect degeneration in the adult melanocytic nevi are less valid for CMN due to their frequent clinical and dermoscopic variability over time. 520 children, 274 females and 246 males, with CMN consecutively arrived to our observation and aged under 13 years – average age of 4.2 years – entered this prospective study. Between June 2005 and October 2011, the children were monitored clinically and dermoscopically. In this population we found a fatal intracranial melanosis, but no cutaneous melanoma. The data from this case study suggest that 1- infants with multiple (more than 3) CMN with a diameter greater than 3 cm and randomly distributed throughout the skin surface and those with giant CMN should be investigated for possible leptomeningeal melanosis; 2- parents must learn to caress the CMN to capture the possible occurrence of nodules, which, especially if characterized by hard consistency, must undergo a skin biopsy to rule out the suspicion of melanoma started from dermal component of CMN; 3- it is not so far available in the literature, and the current series confirms it, another clinical or dermoscopic criterion useful for early diagnosis of malignant transformation